The contribution of small grain production to food security in drought prone areas: the case of Zvishavane (2000-2014) - Nciizah, Tendai (Midlands State University, 2014)
The study examines the role of small grain production in promoting food security with particular reference to Zvishavane District in Zimbabwe. Successive droughts, in Zimbabwe compounded by other economic shocks in recent years have resulted in decreased maize productivity amongst the communal farmers most of whom reside in regions IV and V which are considered semi-arid. This has resulted to the prevalence of food insecurity particularly to these semi-arid regions as unreliable rainfall has undermined subsistence farming. The environment in Zvishavane is no longer conducive for maize production due to unfavourable weather patterns. This has given rise to the need to find alternative food crops, which may be suitable for these areas. Generally, research in the world indicates that sorghum and millet have the potential to end chronic food insecurity in semi-arid areas because of their drought resistance. The study argues that there is need to incorporate small grains in semi-arid areas like Zvishavane. The study shows how small grains have been adopted in Zvishavane and the impact that small grains have on food security as they can enhance food accessibility, utilization, stability and availability. Small grain production can be the way forward in the provision of food security in drought prone areas like Zvishavane rural.